Development of Integrated Natural Science Practicum Guide Integrated Inquiry Approach to Improve Student Learning Outcomes - Rezki Maya Ananda; Marham Sitorus; Ramlan Silaban (BIRCU, 2021)
This study aims to obtain a practicum guide for Integrated Natural Sciences in SMP integrated with guided inquiry approach. This research is a research and development research and experiment. The population in this study were all students of class VIII SMP Negeri 2 Padangsidimpuan. The instrument used was a feasibility questionnaire based on the National Education Standards Agency, a feasibility questionnaire based on conformity with the guided inquiry learning model, cognitive test instruments, critical thinking skills test instruments, and skills observation sheets. The research data were analyzed using independent sample T-test and correlation test with SPSS 21 for windows at a significance of 0.05 with tcount> ttable and rcount> rtable. The results showed that: the Integrated Natural Science book in schools still has shortcomings so that it needs to be developed, the practicum manual that has been developed in Integrated Natural Science learning class VIII semester I is feasible based on the National Education Standards Agency and is in accordance with the model Guided inquiry learning, students' skills are more developed than students using Integrated Natural Science books in schools, student learning outcomes are better than student learning outcomes using Integrated Natural Science books in schools, thinking ability level The critical thinking ability of students is higher than the critical thinking skills of students using the Integrated Natural Science book in schools, there is a significant relationship between skills and the improvement of student learning outcomes and there is a significant relationship between the level of critical thinking skills of students with an increase in student learning outcomes.